Management of oligometastatic and oligoprogressive epidermal growth factor receptor mutated non-small cell lung cancer patients: state of the art of a combined approach - Francesca Di Pressa; Fabiana Perrone; Anna Benini; Frank Lohr; Marcello Tiseo; Alessio Bruni (Open Exploration Publishing Inc., 2024)
Recently, the development of targeted therapy approaches such as those based on tyrosine kinase inhibitor (TKI) greatly improved the clinical outcomes of patients affected by oncogene addicted advanced non-small cell lung cancer (NSCLC). Similarly, the improvement of radiation therapy techniques has permitted to deliver high radiation doses to a limited number of metastatic target lesions (oligopersistent or oligoprogressive), with limited high-dose normal tissue exposure that leads to low severe toxicity rates. The aim of this narrative review was to provide an overview of the currently established definition of oligometastatic and oligoprogressive disease, to define first line and subsequent lines targeted therapies and the role of consolidative non-invasive local ablative treatments (LATs) in these settings. The potential benefit of local treatment (LT) such as radiotherapy (RT) or surgery might be represented by an overall reduction of switching to subsequent systemic treatments lowering the risk of further systemic dissemination. Further randomized clinical trials will clarify the role of LT and their correct timing in relation to systemic targeted therapies.